Implementasi Kebijakan Proyek Strategis Nasional Jalan Tol Serang - Panimbang - Utami, Rina Nur; Wicaksana, Harits Hijrah; Bratakusumah, Deddy Supriady; Hidayat, Yahya Rachmana (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2024)
The purpose of this research is to analyze the implementation of policies in one of the National Strategic Projects (NSP) the Serang Panimbang Toll Road. located in Banten Province. The implementation of the NSP policy for the Serang Panimbang Toll Road aims to improve accessibility to the Special Economic Zone (SEZ) in the tourism sector in Tanjung Lesung. Additionally, the Serang Panimbang Toll Road serves as an effort to optimize transportation infrastructure, enhance the smoothness of economic connectivity for communities, including those from the industrial and tourism sectors in Banten Province. Using the qualitative-descriptive method and the six aspects of Van Metter and Van Horn as indicators, this research will capture the implementation of the National Strategic Project, the Serang Panimbang Toll Road policy. Data obtained by the researcher will be from desk study, questionnaires, and/or interviews with Implementers consisting of the Ministry of Public Works and Public Housing, PT. Wijaya Karya Serang Panimbang as the Business Entity, and the Community of Cibadak Sub-district, Lebak Regency, located within a 5 km radius from the Rangkasbitung Toll Gate, which is the endpoint of section 1 of the Serang Panimbang Toll Road. The research findings indicate that the implementation of the National Strategic Project policy for the Serang Panimbang Toll Road has not yet achieved the set targets. Although coordination and communication among implementing agencies have been effective in finding solutions to address arising conflicts, the implementation of this NSP policy has also experienced delays of approximately two years. These delays are attributed to issues regarding the legality of land owned by the community and problems with financing for section 3, which originates from lenders in China.